CENTRAL ASIA PLUS JAPAN DIALOGUE: ITS ROLE IN JAPAN’S STRATEGY IN CENTRAL ASIA - Dobrinskaya, Olga (WILAYAH: The International Journal of East Asian Studies, 2024)
The article researches the Central Asia and Japan Dialogue (CAJ) which was established in 2004 with the aim of fostering intraregional integration and increasing Japan’s role in the region. It analyses the role it plays in Japan’s strategy in Central Asia, in the way it contributes to the realisation of Japan’s foreign policy goals towards the region. In almost 20 years CAJ has become a permanent framework for discussions which combines official dialogue and informal track and covers wide spectrum of issues, from political agenda to development assistance. CAJ has become instrumental in outlining the areas of practical cooperation although it did not lead to full scale economic integration of the countries of the region. CAJ is an important venue for discussing security agenda as well as maintaining Japan’s engagement in the issues of Afghanistan. Political agenda of CAJ has been restrained as it reflects Japan’s awareness of the close relationship of the Central Asian states with China and Russia, however, in times when Japan’s relations with China and Russia are characterized by a certain level of tensions, Tokyo tends to use CAJ to gain CA supports vis-à-vis these states. . Global issues are less controversial and are usually discussed multilaterally.